Pathological and Molecular Features of Glioblastoma and Its Peritumoral Tissue - D’Alessio, Alessio (Cancers (Basel), 2019)
Glioblastoma (GBM) is one of the most aggressive and lethal human brain tumors. At present, GBMs are divided in primary and secondary on the basis of the mutational status of the isocitrate dehydrogenase (IDH) genes. In addition, IDH1 and IDH2 mutations are considered crucial to better define the prognosis. Although primary and secondary GBMs are histologically indistinguishable, they retain distinct genetic alterations that account for different evolution of the tumor. The high invasiveness, the propensity to disperse throughout the brain parenchyma, and the elevated vascularity make these tumors extremely recidivist, resulting in a short patient median survival even after surgical resection and chemoradiotherapy. Furthermore, GBM is considered an immunologically cold tumor. Several studies highlight a highly immunosuppressive tumor microenvironment that promotes recurrence and poor prognosis. Deeper insight into the tumor immune microenvironment, together with the recent discovery of a conventional lymphatic system in the central nervous system (CNS), led to new immunotherapeutic strategies. In the last two decades, experimental evidence from different groups proved the existence of cancer stem cells (CSCs), also known as tumor-initiating cells, that may play an active role in tumor development and progression. Recent findings also indicated the presence of highly infiltrative CSCs in the peritumoral region of GBM. This region appears to play a key role in tumor growing and recurrence. However, until recently, few studies investigated the biomolecular characteristics of the peritumoral tissue. The aim of this review is to recapitulate the pathological features of GBM and of the peritumoral region associated with progression and recurrence.